Human papillomavirus infection among Bangladeshi women with cervical intraepithelial neoplasia and chronic cervicitis - Khandker, Elisha; Khan, Mansura; Chowdhury, Ahesh Kumar (IMC Journal of Medical Science, 2017)
Background and objectives: Cervical cancer is one of the leading causes of morbidity and mortality. Human papillomavirus (HPV) is known to be associated with cervical intraepithelial neoplasia (CIN) and cancer. The objective of the present study was to determine the rate of HPV infection among the Bangladeshi women with different grades of CIN and cancer. Methods: Women aged 20 to 55 years, diagnosed as a case of chronic cervicits, cervical intraepithelial neoplasia (CIN) or invasive cancer by Papanicolaou (Pap) smear and colposcopy directed biopsy were enrolled in the study. High and intermediate risk oncogenic HPV were detected in cervical samples by real time PCR (rt-PCR). Results: Seventy two women with chronic cervicitis and different grades of CIN were included in the study. Out of 72 cases, 28 (38.9%) and 44 (61.1%) had chronic cervicitis and CIN respectively. Overall, the HPV infection rate was 43.1% (95% CI= 32%-54%) among the study population. CIN cases had significantly high (p<0.01) HPV infection (78.6%; 95% CI=60%-89%) compared to cases with chronic cervicitis (18.2%; 95% CI=11.1%-34.5%). Women between the age of 20-30 years had the highest positive rate (50.0%) followed by 31- 40 years age group (43.6%). All CIN grade 2 and 3 had HPV infection. Conclusion: The study showed that HPV was strongly associated with different grades of CIN. Specific HPV types should be determined to find out the most prevalent HPV types among the Bangladeshi women with CIN and cervical cancers. IMC J Med Sci 2016; 10(1): 29-32